A correlation study between mean platelet volume and platelet aggregation study in acute coronary syndrome patients - PT Navya; M Natarajan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Platelets play an important role in cardiovascular disease mainly in the development of acute thrombotic events. Elevated platelet indices have been proposed as a risk factor for acute coronary syndrome (ACS). It remains uncertain whether increased platelet indices are the result or the cause of ACS. Aim and Objective: This study aimed to correlate mean platelet volume (MPV) and platelet aggregation response to know the functional status of platelets based on their size. Materials and Methods: A total of 50 patients with ST-segment elevation ACS (STE-ACS) or non-ST-segment elevation ACS (NSTE-ACS) were included and their MPV was measured and platelet aggregometry was performed. Patients were divided into two groups, patients with MPV ≤9.1 fl as group 1 and those with MPV >9.1 fl as group 2. The mean maximum platelet aggregation response (MMPAR) with ADP, Collagen, and Epinephrine, of both the groups, were compared. MMPAR to ADP, Collagen, and Epinephrine in group 1 was 74.47%, 66.13%, and 72.9%, respectively, and in group 2, 72.94%, 59.97%, and 72.43%, respectively. There was no statistically significant difference in the MMPAR to ADP, Collagen, and Epinephrine among the two groups. Conclusion: Increased MPV does not indicate the platelets are hyperreactive. An increase in MPV may be because of the increased release of immature platelets from bone marrow as there is increased consumption of platelets at the site of thrombus formation in ACS.